THE EFFECT OF GUIDED INQUIRY LEARNING MODEL ON STUDENTâS LEARNING OUTCOMES ON HARMONIC VIBRATION TOPIC IN CLASS X SMA NEGERI 1 BERASTAGI A.Y 2017/2018 - Sijabat, Maylastri; Sani, Ridwan A (JURNAL IKATAN ALUMNI FISIKA UNIVERSITAS NEGERI MEDAN, 2018)
The purpose of this research is to know the studentâs learning outcomes using guided inquiry learning model in harmonic vibration topic of class X SMA N 1 Berastagi. The type of this research is quasi-experimental which using pre-test and post-test design. The subject of this research are students of class X MIPA 4 that consists of 33 students as experiment class and X MIPA 5 that consist of 33 students as control class. The object in this research is studentâs learning outcomes. The data of pretestÂ  in experiment class is 23.66 and the average score of pretest in control class is 24.15. The experiment class is taught by guided inquiry learning model and control class is taught by conventional learning that get the result of average score in experiment class is 73.75 and average score in control class is 63.18. Based on hypothesis test is obtained that Ha is accepted and it means there is effect of guided inquiry learning model on studentâs learning outcomes on harmonic vibration topic in class X SMA N 1 Berastagi A.Y 2017/2018